2006
DOI: 10.1002/dvdy.21013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gdnf haploinsufficiency on rate of migration and number of enteric neural crest‐derived cells

Abstract: The enteric nervous system arises predominantly from vagal level neural crest cells that migrate into the foregut and then colonize the entire length of the gastrointestinal tract. Previous studies have demonstrated that glial cell line-derived neurotrophic factor (GDNF) promotes the migration of enteric neural crest-derived cells (ENCs) in vitro, but a role for GDNF in the migration of ENCs in vivo has yet to be demonstrated. In this study, the effects of Gdnf haploinsufficiency on ENC rate of migration and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…In avians, the percentage of neurons rises from zero at E4.5 to around 55% at E6 (18). In the mouse midgut, neurogenesis occurs within a small proportion of NC-derived cells as early as E10.5 (21). It rises dramatically to reach a quarter of these cells by E12.5 and to 45% at E14.5 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In avians, the percentage of neurons rises from zero at E4.5 to around 55% at E6 (18). In the mouse midgut, neurogenesis occurs within a small proportion of NC-derived cells as early as E10.5 (21). It rises dramatically to reach a quarter of these cells by E12.5 and to 45% at E14.5 (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse midgut, neurogenesis occurs within a small proportion of NC-derived cells as early as E10.5 (21). It rises dramatically to reach a quarter of these cells by E12.5 and to 45% at E14.5 (21). We detected cholinergic neurogenesis within the gut as early as E10.5.…”
Section: Discussionmentioning
confidence: 99%
“…NCC within 300 μm of the wave-front have also been shown to migrate faster than their more rostral neighbours (Druckenbrod and Epstein, 2007). It is clear that the NCC migration wave-front is more sensitive to the influence of the gut microenvironment, as it is these cells within Edn3 mutants and Gdnf heterozygous mice that have a reduced proliferative capacity when compared with the entire population of NCC Flynn et al, 2007). However, data against this critical number model for gut colonisation comes from the work of Sidebotham and colleagues (Sidebotham et al, 2002).…”
Section: /51mentioning
confidence: 99%
“…Randomly chosen fields within the ileum and proximal colon were imaged using a ϫ63 lens and a Bio-Rad MRC 1024 confocal microscope as previously described (Flynn et al, 2007). It has previously been shown that differentiating neurons show strong nuclear expression of Hu, whereas cells that have not started to differentiate into neurons are either Hu-negative or show weak Hu staining in the cytoplasm only .…”
Section: Cell Countmentioning
confidence: 99%